Formation, Existence, And Survival Of Islamic Banking System In India - Mohammed Masood Riswi (Penerbit Hellow Pustaka, 2025)
This study investigates the formation, historical development, and ongoing struggle for the institutional survival of the Islamic banking system in India. Drawing on both primary historical references and contemporary regulatory frameworks, the article examines the deep roots of interest-free financial practices in ancient Indian civilizations, such as the Harappan society, and the contributions of Muslim rulers, including the Cheraman Perumals and Raja Bhoj, who laid the early foundations for Islamic financial ethics. The emergence of structured Islamic financial models in the pre- and post-independence era—such as community-based cooperative credit societies, Baithul Mals, and Muslim funds—is traced to show how Islamic finance has adapted over time to survive in a secular legal and political environment.